2014
DOI: 10.1371/journal.pgen.1004135
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Genomic Characterization Reveals Novel, Therapeutically Relevant Drug Targets in FGFR and EGFR Pathways in Sporadic Intrahepatic Cholangiocarcinoma

Abstract: Advanced cholangiocarcinoma continues to harbor a difficult prognosis and therapeutic options have been limited. During the course of a clinical trial of whole genomic sequencing seeking druggable targets, we examined six patients with advanced cholangiocarcinoma. Integrated genome-wide and whole transcriptome sequence analyses were performed on tumors from six patients with advanced, sporadic intrahepatic cholangiocarcinoma (SIC) to identify potential therapeutically actionable events. Among the somatic event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
274
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 309 publications
(283 citation statements)
references
References 102 publications
6
274
0
3
Order By: Relevance
“…FGFR fusion events have been recently identified in several cancers. Multiple partners have been discovered including BICC1, AFF3, CASP7 and CCDC6 among others [17][18][19][20] . These different partners play an important role in the control of enforced oligomerization and subsequent trans-autophosphorylation and activation of the tyrosine kinase gene involved in the rearrangement 12,17,21 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…FGFR fusion events have been recently identified in several cancers. Multiple partners have been discovered including BICC1, AFF3, CASP7 and CCDC6 among others [17][18][19][20] . These different partners play an important role in the control of enforced oligomerization and subsequent trans-autophosphorylation and activation of the tyrosine kinase gene involved in the rearrangement 12,17,21 .…”
Section: Resultsmentioning
confidence: 99%
“…19). Nonetheless, the incidence of FGFR2 fusions strikingly differs across the iCCA published cohorts, with a range between 50% in small series 17,18 to 10-15% in series of up to 96 patients 19,20,30 . Overall, our cohort consisted of Caucasian patients at early-intermediate stage iCCA amenable for resection, whereas other series mostly refer to Asian patients at more advanced stage of disease 19 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These receptors bind to one of 18 secreted glycoprotein ligands, or fibroblast growth factors (FGFs), to their extracellular domain (71). Several FGFR2 chromosomal fusions, with several genomic partners, have been identified in IHCC (72)(73)(74)(75)(76)(77). Preclinical studies have identified several FGFR2 fusions (FGFR2-PPHLN1, FGFR2-BICC1, FGFR2-TACC3, AHCYL1) specifically in intrahepatic BC, where genomic sequencing identified an incidence ranging up to 50% of intrahepatic BC patients.…”
Section: Fibroblast Growth Factor Receptor (Fgfr)mentioning
confidence: 99%